Analysis of Student Economic Literacy Levels Malang State University - Ahmad Rifki; Wahjoedi Wahjoedi (Journal of Applied Business, Taxation and Economics Research, 2023)
The purpose of this study is to determine the level of economic literacy of Malang State University students. This research is quantitative research with a survey type. The research sample is 80 students from class 2021 who had taken microeconomics and macroeconomics courses. The results of this study indicate that the level of economic literacy of Economics Education students at the State University of Malang is categorized as moderate with a value of 61.13% (60-79%). The total percentage of correct answers from students or respondents with the most correct answers amounted to 56.25% with a total of 45 students in the moderate category. Furthermore, the correct answer with a percentage of 36.25% with a total of 29 students in the low category. While the high category was 6 students with a percentage of 7.5%. The implication of this research is that students need to increase their knowledge and understanding of the economy. This is because supporting their competition and economic literacy greatly affects several aspects of student life. In addition, economic literacy is also needed to make the right economic decisions in everyday life.